The effect of composite resin immersion in red betel leaf (Piper crocatum) decoction on composite resin hardness: Pengaruh perendaman resin komposit pada rebusan daun sirih merah (Piper crocatum) terhadap kekerasan resin komposit - Raflesia, Wikhe Baslen; Sari, Widya Puspita; Anggraini, Netta; Widyawati; Darmawangsa (Makassar Dental Journal, 2025)
Composite resin is a widely used dental restoration material due to its excellent mechanical and aesthetic properties; however, va-rious external factors, including exposure to chemicals in mouthwash, can affect its hardness. Red betel leaf (Piper crocatum) is known to contain phenols and have antibacterial properties, which are often used in oral health care. This article evaluates the ef-fect of immersing composite resin in DSM decoction on its hardness, analyses the impact of immersion duration, and compares its effects on various types of composite resin. This study employs a scoping review method, reviewing literature from data-bases such as Google Scholar, Science Direct, and PubMed from 2015 to 2025. The articles used were selected based on pre-defined inclusion and exclusion criteria, screened using the PRISMA method, and data analysis was conducted by synthesi-sing the results from relevant articles. It was concluded that soaking composite resin in DSM decoction reduces the materi-al's hardness due to the chemical content in DSM and the duration of soaking. Consideration of restorative materials and their use in combination with natural materials such as red betel leaves should be taken into account in dental practice.